2005
DOI: 10.1080/1366880052000323986
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial benefits of work for people with severe and enduring mental health problems

Abstract: Perceptions of the value of work for people with severe and enduring mental health problems have changed frequently over the last two decades. With the new social inclusion agenda manifest in the Disability Discrimination Act and in the NHS modernization agenda, work is once again in vogue. There is a need for a way of evaluating work which draws on its potential contribution to psychological well-being as well as its provision of a valued social role and which is less susceptible to fluctuations in health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
0
9
1
1
Order By: Relevance
“…In summarising the results of both matching procedures, we conclude that One-Euro-Job participation has, on average, no obvious beneficial effect on participants' self-efficacy. Although other studies show that participation in specific training programmes is most beneficial for people with low baseline levels of self-efficacy or poor mental health (Eden and Aviram, 1993;Goodwin and Kennedy, 2005), for almost all the self-efficacy outcomes and samples in our study, we find neither beneficial effects for those with low baseline levels of self-efficacy nor considerable adverse effects for participants with high initial levels of self-efficacy.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In summarising the results of both matching procedures, we conclude that One-Euro-Job participation has, on average, no obvious beneficial effect on participants' self-efficacy. Although other studies show that participation in specific training programmes is most beneficial for people with low baseline levels of self-efficacy or poor mental health (Eden and Aviram, 1993;Goodwin and Kennedy, 2005), for almost all the self-efficacy outcomes and samples in our study, we find neither beneficial effects for those with low baseline levels of self-efficacy nor considerable adverse effects for participants with high initial levels of self-efficacy.…”
Section: Discussioncontrasting
confidence: 98%
“…Taken together, we find neither noteworthy beneficial effects nor unfavourable One-Euro-Job participation effects on participants' self-efficacy, which is consistent with our first hypothesis. Goodwin and Kennedy (2005) demonstrate that work helps restore self-confidence in persons with severe and enduring mental health problems. Therefore, it might be assumed that One-Euro-Job participation leads to a beneficial increase in self-efficacy for those with low baseline levels self-efficacy but has adverse effects for participants with high baseline levels of self-efficacy.…”
Section: Resultsmentioning
confidence: 96%
“…Employment for individuals with mental health needs is vital, not just because of the direct improvements in activity and social contact but also because work may promote self-esteem, quality of life and integration into the community (Bond, Resnick, Drakes, Bebout, Xie and Haiyi, 2001;Goodwin and Kennedy, 2005;Rogers, Sciarappa, McDonald, Wilson and Danley, 1995). However, limited studies have investigated employer's attitudes towards individuals with mental health needs.…”
Section: Introductionmentioning
confidence: 99%
“…For people with psychiatric diagnoses, employment is known to be a meaningful indicator of functioning in that it allows access to a valued social role [7] and a sense of meaning and recovery [8]. Additionally, a recent analysis found that having a working-aged member of a household with severe mental illness is associated with a 3.10 increase in the odds of household poverty [9].…”
Section: Introductionmentioning
confidence: 99%